2002
DOI: 10.1017/s0022112002008868
|View full text |Cite
|
Sign up to set email alerts
|

Buoyant gravity currents along a sloping bottom in a rotating fluid

Abstract: The dynamics of buoyant gravity currents in a rotating reference frame is a classical problem relevant to geophysical applications such as river water entering the ocean. However, existing scaling theories are limited to currents propagating along a vertical wall, a situation almost never realized in the ocean. A scaling theory is proposed for the structure (width and depth), nose speed and flow field characteristics of buoyant gravity currents over a sloping bottom as functions of the gravity current tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
161
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(193 citation statements)
references
References 29 publications
27
161
2
Order By: Relevance
“…As mentioned previously, the ratio of the isopycnal slope to the bathymetric slope sЈ/s is the principle parameter controlling the strength of the interaction between the current and the bathymetry (Yankovsky and Chapman 1997;Lentz and Helfrich 2002). This parameter is large (small) when the bathymetric slope is gentle (steep) relative to the slope of the isopycnals.…”
Section: Comparison With Oceanic Observationsmentioning
confidence: 93%
See 3 more Smart Citations
“…As mentioned previously, the ratio of the isopycnal slope to the bathymetric slope sЈ/s is the principle parameter controlling the strength of the interaction between the current and the bathymetry (Yankovsky and Chapman 1997;Lentz and Helfrich 2002). This parameter is large (small) when the bathymetric slope is gentle (steep) relative to the slope of the isopycnals.…”
Section: Comparison With Oceanic Observationsmentioning
confidence: 93%
“…Several authors have proposed scale variables that can be used to classify buoyant coastal currents using parameters that can be controlled or measured at the source. The most convenient for the purposes of this study are those derived and tested in a series of laboratory experiments by Lentz and Helfrich (2002). An idealized representation of the flow studied by these authors is shown in Fig.…”
Section: Review Of Relevant Dynamical Scalesmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies of coastal currents (e.g. Griffiths & Hopfinger 1983, Griffiths 1986, Davies, Jacobs & Mofor 1993, Simpson 1997, Thomas & Linden 1998, Boyer, Haidvogel & Pèrenne 2001, Avicola & Huq 2002, Lentz & Helfrich 2002, Avicola & Huq 2003a,b, Rivas, Velasco Fuentes & Ochoa 2005, Horner-Devine et al 2006 have dealt with the current speed, depth and width, and examined their stability and the effects of bottom topography on the current dynamics or the characteristics of the gyre that forms near the estuary where the river water enters the ocean. Here we examine the response of the propagation speed of the currents following a change of the volumetric discharge rate of fresh water at the source.…”
Section: Introductionmentioning
confidence: 99%